2015
DOI: 10.1111/anec.12288
|View full text |Cite
|
Sign up to set email alerts
|

Fever‐Induced Brugada Syndrome Is More Common Than Previously Suspected: A Cross‐Sectional Study from an Endemic Area

Abstract: Our study showed a highest prevalence of fever induced BrS ever reported. A larger study of prevalence, risk stratification, genetic test and management of fever-induced BrS should be done, especially in an endemic area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 19 publications
2
33
0
3
Order By: Relevance
“…The prevalence of fever-induced Brugada was found to be 2% in febrile patients in an emergency department in Israel and 4% in Thailand [13,14]. Interestingly, both age (mean 47, range 19-81) and male predominance (86%) of the patients in these two studies were similar to those found in large, nonfebrile-induced BrS cohorts.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…The prevalence of fever-induced Brugada was found to be 2% in febrile patients in an emergency department in Israel and 4% in Thailand [13,14]. Interestingly, both age (mean 47, range 19-81) and male predominance (86%) of the patients in these two studies were similar to those found in large, nonfebrile-induced BrS cohorts.…”
Section: Introductionsupporting
confidence: 66%
“…Recently, the prevalence of a type I Brugada pattern in unselected febrile patients was found to be 2-4% [13,14]. All patients were free of cardiac events up to presentation and during follow-up of 12-30 months.…”
Section: Spontaneous Vs Drug/fever-induced Brugada Patternmentioning
confidence: 93%
“…Although J waves are accentuated or induced by both hypothermia and fever, 33, 34, 134-139 the development of arrhythmias in ERS is much more sensitive to hypothermia, and arrhythmogenesis in BrS appears to be promoted only by fever. 33, 34, 138, 139 Hypothermia has been reported to increase the risk of VF in ERS, 33, 34, 134, 135, 140 and fever is well recognized as a major risk factor in BrS.…”
Section: Similarities and Difference Between Brs And Ersmentioning
confidence: 98%
“…33, 34, 138, 139 Hypothermia has been reported to increase the risk of VF in ERS, 33, 34, 134, 135, 140 and fever is well recognized as a major risk factor in BrS. 138, 139 It is noteworthy that hypothermia can diminish the manifestation of a BrS ECG when already present. 141, 142 …”
Section: Similarities and Difference Between Brs And Ersmentioning
confidence: 99%
“…ERS patients are at greater risk of VF during hypothermia as well as in the event of an acute myocardial infarction . BrS patients are known to be at greater risk of VF in febrile states as well as when accompanied by an ER pattern in the inferolateral leads . Available data suggest that mild therapeutic hypothermia to a temperature of 34°C can be used safely in cases of BrS …”
Section: Similarities and Difference Between Brs And Ersmentioning
confidence: 99%